YouTube Disintermediation by Public Officials: Digital Regulatory Challenges for Local Television Sustainability - Wulandari, Ayu; Pramiyanti, Alila; Hidayat, Dasrun; Rina, Nofha (Komunikator, 2026)
The transformation of public officials’ communication via YouTube has intensified information disintermediation. This study examines the communication practices of Dedi Mulyadi, who conveys public information directly, bypassing conventional media channels. The urgency of this research stems from the critical need for regulatory frameworks governing YouTube usage, as official disintermediation exacerbates the economic strain on local television. The novelty of this study lies in its identification of regulatory lacunae regarding the digital activities of public officials and their subsequent implications for the viability of local broadcasters. Employing a qualitative, descriptive methodology, data were gathered through in-depth interviews with key stakeholders across the media, regulatory bodies, government, and academia. The findings reveal that such disintermediation fosters regulatory asymmetry, positioning YouTube as a ‘pseudo-media’ entity exempt from the social and ethical mandates imposed on local television. Consequently, this research proposes a platform-neutral, impact-based reconstruction of broadcasting regulations. It extends the gatekeeping theory within the digital ecosystem and provides a strategic policy foundation for regulators to integrate public accountability standards into officials’ official YouTube accounts, thereby ensuring a balanced local media landscape.